Investigación gravimétrica y magnética a través del istmo de panamá (noroeste colombiano) (1969)
Regional gravity and magnetic surveys have been conducted in northwestern Colombia across the extreme southeastern end of the Isthmus of Panamá along the proposed Atrato-Truandó interoceanic canal route.  In the Serranía de Baudó, the Pacific coast range, vertical intensity magnetic anomalies are of steep gradient and large amplitude, up to 3.000 gammas, over basalts and other mafic igneous rocks that form the pre-Eocene basement. Magnetic anomalies are of very low amplitude over the thick sequence or Tertiary sedimentary rocks in the basin along the Rio Atrato. A small magnetic anomaly of a few hundred gammas is present over the Sautatá arch near Loma Teguerre.  From there, northeast to the Golfo de Urabá, magnetic anomalies are of low amplitudes. The regional magnetic field increases northeastward by about 2.000 gammas from Curiche Beach, on the Pacific Coast, to the Atrato delta, on the Golfo de Urabá.  Bouguer anomalies attain values as high as + 130 mgals over the pillow basalts of the Serranía de Baudó. A small residual negative anomaly of about 10 mgals is present over sedimentary rocks in the Nercua graben. Bouguer anomaly values decrease to -5mgals near Río Sucio, at the axis of the sedimentary basin along the Atrato and then increase to + 90 mgals over the Sautatá arch near Loma Teguerre.  From there they decrease to - 40 mgals at Turbo over the Tertiary sedimentary basin developed near the Golfo de Urabá.  From these data, the following conclusions can be drawn: (1) The Sautatá arch serves as a structural link between the Andean Cordillera Occidental and the Serranía del Darien of Panamá. (2) Prevalence of pillow basalts and Bouguer anomaly values in excess of + 100 mgals suggest that the basement of the Serrania de Baudó is a raised segment of oceanic crust. (3) Sediments in the Tertiary basins were deposited directly on oceanic crust and on rocks of a late Mesozoicearly Tertiary eugeosyncline, remnants of wich are exposed in the Cordillera Occidental.